A virtual sizing tool for mitral valve annuloplasty. (20th April 2016) - Rausch, Manuel K.; Zöllner, Alexander M.; Genet, Martin; Baillargeon, Brian; Bothe, Wolfgang; Kuhl, E.
Summary: Functional mitral regurgitation, a backward leakage of the mitral valve, is a result of left ventricular growth and mitral annular dilatation. Its gold standard treatment is mitral annuloplasty, the surgical reduction in mitral annular area through the implantation of annuloplasty rings. Recurrent regurgitation rates may, however, be as high as 30% and more. While the degree of annular downsizing has been linked to improved long‐term outcomes, too aggressive downsizing increases the risk of ring dehiscences and significantly impairs repair durability. Here, we prototype a virtual sizing tool to quantify changes in annular dimensions, surgically induced tissue strains, mitral annular stretches, and suture forces in response to mitral annuloplasty. We create a computational model of dilated cardiomyopathy onto which we virtually implant annuloplasty rings of different sizes. Our simulations confirm the common intuition that smaller rings are more invasive to the surrounding tissue, induce higher strains, and require larger suture forces than larger rings: The total suture force was 2.2 N for a 24‐mm ring, 1.9 N for a 28‐mm ring, and 0.8 N for a 32‐mm ring. Our model predicts the highest risk of dehiscence in the septal and postero–lateral annulus where suture forces are maximal. These regions co‐localize with regional peaks in myocardial strain and annular stretch. Our study illustrates the potential of realistic predictive simulations in cardiac surgery to identify areas at risk for dehiscence, guide the selection of ring size and shape, rationalize the design of smart annuloplasty rings and, ultimately, improve long‐term outcomes after surgical mitral annuloplasty. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Annuloplasty is a surgical procedure to repair a leaking heart valve through the implantation of annuloplasty rings. This publication introduces a virtual sizing tool to quantify changes in annular dimensions, surgically induced tissue strains, mitral annular stretches, and suture forces in response to mitral annuloplasty. Our new tool can help identify critical regions, guide the selection of ring size and shape, rationalize the design of smart annuloplasty rings and, ultimately, improve long‐term outcomes of surgical mitral annuloplasty.